(untitled) (Journal of Educational Sciences, 2017)
The question of the role of the family as the main social factor influencing the formation of the person is very important. This article discusses:the notion of complete and incomplete family, the growing number of single-parent families, sources of single-parent families, single-parent families problems, such as socio – economic, educational, medical and psychological, as well as the socialization of children. The author critically assesses and warns about the appearance of negative sources of singleparent families, such as social and civil immaturity of the couple, their irresponsible, frivolous relationship towards the family, as well as the increase in the number of forced marriages, as a result of pregnancy and childbirth. In this connection the author underline the role of the social educator, the practical activity is aimed at psychological and educational support for children and adults, personality development, human rehabilitation. To this end the author suggests the search for new models of education for younger generation, education raises the problem of the individual in an open social environment that requires close cooperation between all the educational institutions of our society – school, family, labor groups and the public.